Space, Time and Language in Plutarch - Georgiadou, Aristoula; Oikonomopoulou, Katerina (Millennium-Studien / Millennium Studies, 2017)
This collection of essays by a team of international scholars offers a wide-ranging examination of the key concepts of 'space and time' in the work of the Greek biographer and philosopher Plutarch of Chaeronea (1st-2nd centuries CE). Combining philological and socio-cultural approaches, the essays demonstrate how space and time can shed new light on Plutarch's biographical, philosophical, religious and political thought.